Toni Morrison and Ralph Ellison’s Oraliture: Writing Fiction against the Grain - Sy, Ousseynou (Metacritic Journal for Comparative Studies and Theory, 2019)
This paper attempts to demonstrate how Ellison and Morrison’s prose is interwoven with markers of oral literature, oraliture or orature. This oraliture draws upon African culture. To better deconstruct the Africanism or the different fragments of African culture in the fiction of the two writers under study, I focus on Henry Louis Gates's The Signifying Monkey and Jennings' Toni Morrison and the Idea of Africa. For example, fairy tales, the sermons of Homer Barbee and the Jazz music of Louis Armstrong, are powerful elements of oraliture which aesthetically hybridize the novelistic discourse. This oraliture becomes a revitalizing mechanism through which Ellison and Morrison subvert not only the Eurocentric aesthetic novelistic tradition but also convey their own political agenda, which represents a call for a more democratic society in a white structured world. Africanism functions, then, as a poetics of visibility that offers to Ellison and Morrison a parallel discursive arena wherein they can question historiography and invent and circulate a counter-discourse to represent themselves and express their concerns and identities. The oraliture is not subordinate to the novelistic discourse, but rather grafts itself on the latter as an aesthetically and politically loaded counterpart.